2007
DOI: 10.1523/jneurosci.3812-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contribution of Nestin-Expressing Stem Cells to Adult Neurogenesis

Abstract: Understanding the fate of adult-generated neurons and the mechanisms that influence them requires consistent labeling and tracking of large numbers of stem cells. We generated a nestin-CreER T2 /R26R-yellow fluorescent protein (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
587
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(622 citation statements)
references
References 45 publications
27
587
3
Order By: Relevance
“…We did not observe increases in Hes5CreER T2 -derived polymorphic astrocytes (S100β + ) over time, confirming results from clonal analysis of SGZ NSCs 11 . We also did not observe Hes5 + NSC-derived oligodendrocytes; hence, in accordance with other reports, adult DG NSCs are mainly neurogenic and do not contribute majorly to gliogenesis in vivo 6,11,14,17,47,49 .…”
Section: Hes5creersupporting
confidence: 93%
See 1 more Smart Citation
“…We did not observe increases in Hes5CreER T2 -derived polymorphic astrocytes (S100β + ) over time, confirming results from clonal analysis of SGZ NSCs 11 . We also did not observe Hes5 + NSC-derived oligodendrocytes; hence, in accordance with other reports, adult DG NSCs are mainly neurogenic and do not contribute majorly to gliogenesis in vivo 6,11,14,17,47,49 .…”
Section: Hes5creersupporting
confidence: 93%
“…Amplification in the lineage is thought to occur through multiple symmetric divisions of IPs, primarily at the type-2a stage 5,42,43 . To shed light on the neurogenic process, several transgenic mouse lines have been used to lineage trace NSCs in a controlled manner 10,[13][14][15][16][17][18][44][45][46][47] . However, the expression of most transgenes is not restricted in the SGZ to NSCs, resulting in labeling of more differentiated cell types 5,20 .…”
Section: Hes5creermentioning
confidence: 99%
“…In the adult rodent brain, neural stem cells (NSCs) reside in two main niches, the subventricular zone (SVZ) and the dentate gyrus of the hippocampus (Doetsch et al, 1999;Anthony et al, 2004;Zhao et al, 2008). NSCs in the hippocampus give rise to new granule layer neurons that integrate into functional neuronal circuits (Kaplan and Bell 1984;Kempermann et al, 1998a;Gould et al, 1999;Song et al, 2002;Lagace et al, 2007) and are critical for such cognitive functions as learning and memory formation (Shors et al, 2001;Kee et al, 2007;Imayoshi et al, 2008;Zhang et al, 2008;Clelland et al, 2009). Deep layer neurons of the olfactory bulb are continuously replaced by neurons generated from the NSCs in the SVZ and play essential roles in odor discrimination and odor memory (Gheusi et al, 2000;Enwere et al, 2004;Lagace et al, 2007;Breton-Provencher et al, 2009).…”
mentioning
confidence: 99%
“…NSCs in the hippocampus give rise to new granule layer neurons that integrate into functional neuronal circuits (Kaplan and Bell 1984;Kempermann et al, 1998a;Gould et al, 1999;Song et al, 2002;Lagace et al, 2007) and are critical for such cognitive functions as learning and memory formation (Shors et al, 2001;Kee et al, 2007;Imayoshi et al, 2008;Zhang et al, 2008;Clelland et al, 2009). Deep layer neurons of the olfactory bulb are continuously replaced by neurons generated from the NSCs in the SVZ and play essential roles in odor discrimination and odor memory (Gheusi et al, 2000;Enwere et al, 2004;Lagace et al, 2007;Breton-Provencher et al, 2009). In humans, adult neural progenitors have been identified in the dentate gyrus and lateral ventricles (Eriksson et al, 1998;Kukekov et al, 1999;Roy et al, 2000;Sanai et al, 2004;Curtis et al, 2007), although their role in cognition has not been established.…”
mentioning
confidence: 99%
“…Once the neuroblasts reach the subependymal region of the olfactory bulb, they disperse radially and differentiate into granule and periglomerular neurons (Luskin, 1993, Lois&Alvarez-Buylla, 1994, Lois, et al, 1996, Thomas, et al, 1996, Curtis, et al, 2007. Studies have shown that olfactory granule and periglomerular cells are continuously added to the olfactory bulb to both increase total cell number over time in these layers as well as replace pre-existing cells (Lagace, et al, 2007, Imayoshi, et al, 2008. The function of persistent olfactory bulb neurogenesis is largely unknown, but increasing evidence supports a role for the new neurons in olfactory memory and odour discrimination (Gheusi, et al, 2000, Petreanu, et al, 2002, Rochefort, et al, 2002.…”
Section: Introductionmentioning
confidence: 99%